Hyperbolic discounting and the time-consistent solution of three canonical environmental problems - Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
In this paper I propose a time-consistent method of discounting hyperbolically that contains the discount rate implied by Gamma discounting as a special case. I apply the discounting method to three canonical environmental problems: (i) optimal renewable resource use, (ii) the tragedy of the commons, (iii) economic growth and pollution. I then compare results with those for conventional exponential discounting using the normalization that both methods provide the same present value of an infinite constant flow. I show that, irrespective of potentially high initial discount rates, time-consistent hyperbolic discounting leads always to a steady state of maximum yield, or, if the environment enters the utility function, a steady state where the Green Golden Rule applies. While (asymptotic) extinction is a real threat under exponential discounting it is impossible under time-consistent hyperbolic discounting. This result is also confirmed for open access resources. In a model of economic growth and pollution, hyperbolic discounting establishes the Golden Rule of capital accumulation and the Modified Green Golden Rule.
Is replaced by the following version: http://hdl.handle.net/10419/170719
Keywords: D60; D90; Q20; Q50; Q58; O40; 330; discounting; time-consistency; renewable resource use; property rights; growth; pollution